Development strategy of ecological agriculture - Чухліб, Ю. О. (Scientific Progress & Innovations, 2012)
The preconditions and developed theoretical and methodological principles of ecological agriculture based on systemically-ecological approach have been analyzed. The factors that determine the organizational, technological, economic and social aspects of transition of agricultural production to ecological method of management have been defined. It has been noted that the agricultural production should be considered as a sustainable environmental and economic system, elements of which operate as one interconnected whole.